How to really fool yourself illusions for all your senses - Cobb, Vicki; Wolk-Stanley, Jessica (New York : John Wiley & Sons, Inc., 1999)
Demonstrations accompanied by explanations illustrate how and why the senses can be fooled.
Includes index.
8 - 18 years
Keywords: Senses and sensation; Perception; Optical illusions; Science -- Experiments -- Juvenile literature; Hallucinations and illusions -- Juvenile literature